On being a physician to celebrities! - Sadananda B Naik (Wolters Kluwer Medknow Publications, 2023)
It is rewarding but often very challenging to be the physician to a celebrity and there are many virtues as well as shortcomings in this position of importance. This is a short write-up on what it takes to be a doctor to a celebrity.